Treatment of acute cough/lower respiratory tract infection by antibiotic class and associated outcomes: a 13 European country observational study in primary care. - Butler, C; Hood, K; Kelly, M; Goossens, H; Verheij, T; Little, P; Melbye, H; Torres, A; Mölstad, S; Godycki-Cwirko, M; Almirall, J; Blasi, F; et al. (2010)
OBJECTIVES: Acute cough/lower respiratory tract infection (LRTI) is one of the commonest reasons for consulting and antibiotic prescribing. There are theoretical reasons why treatment with particular antibiotic classes may aid recovery more than others, but empirical, pragmatic evidence is lacking. We investigated whether treatment with a particular antibiotic class (amoxicillin) was more strongly associated with symptom score resolution and time to patients reporting recovery than each of eight other antibiotic classes or no antibiotic treatment for acute cough/LRTI. METHODS: Clinicians recorded history, examination findings, symptom severity and antibiotic treatment for 3402 patients in a 13 country prospective observational study of adults presenting in 14 primary care research networks with acute cough/LRTI. 2714 patients completed a symptom score daily for up to 28 days and recorded the day on which they felt recovered. A three-level autoregressive moving average model (1,1) model investigated logged daily symptom scores to analyse symptom resolution. A two-level survival model analysed time to reported recovery. Clinical presentation was controlled for using clinician-recorded symptoms, sputum colour, temperature, age, co-morbidities, smoking status and duration of illness prior to consultation. RESULTS: Compared with amoxicillin, no antibiotic class (and no antibiotic treatment) was associated with clinically relevant improved symptom resolution (all coefficients in the range -0.02 to 0.01 and all P values greater than 0.12). No antibiotic class (and no antibiotic treatment) was associated with faster time to recovery than amoxicillin. CONCLUSIONS: Treatment by antibiotic class was not associated with symptom resolution or time to recovery in adults presenting to primary care with acute cough/LRTI.